Mobile Digital Waybill in Organization and Management Of City Public Transport - Piotr KISIELEWSKI (Communications of International Proceedings, 2025)
The article presents the issue of the possibility of replacing the traditionally paper waybill document in public transport with a digital version of this document. The literature review has revealed there are practically no scientific publications for the waybill in city public transport, and the Internet sources are rare. The waybill as a required transport document occurs both in freight and passenger transport. In freight transport, the waybill, also known as the consignment note, is an important supply chain management document, which has received numerous digital implementations. The mobile waybill has been functioning for several years as an electronic document for almost all rail operators in Poland. For almost 30 years, when the first computer programs supporting the planning, dispatch and settlement of transport were implemented, until today it has not been possible to abandon paper waybills in urban public transport, apart from a few public transport operators in cities who have implemented a mobile electronic waybill in the last two years. Based on process engineering the paper presents the concept of a digital waybill as a mobile application for city public transport drivers, which is also a medium for a wide exchange of information online between the company, its transport dispatch center and the drivers. The concepts provided has already found successful implementation in public transport systems of several cities in Poland.
Keywords: digital waybill; transport dispatch; urban public transport